2019
DOI: 10.1155/2019/1807287
|View full text |Cite
|
Sign up to set email alerts
|

Ipsi- and Contralateral Moxibustion Generate Similar Analgesic Effect on Inflammatory Pain

Abstract: The aim of this study was to investigate whether contralateral moxibustion would generate a similar analgesic effect with ipsilateral moxibustion. Contra- and ipsilateral moxibustion were separately applied to Zusanli (ST36) acupoints of inflammatory pain mice. The analgesic effect was evaluated, respectively, by licking/biting time (LBT) of formalin-induced inflammatory pain and thermal withdrawal latency (TWL) of complete Freund’s adjuvant- (CFA-) induced inflammatory pain. For formalin-induced pain, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Through the measurement of the above three pain behaviors, it was verified that the KSM is also suitable for the study of acupuncture analgesia. The analgesic effect of the opposing needling method is equivalent to the analgesic effect of acupuncture on the operated side, which is similar to the results in many other research researches [ 19 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Through the measurement of the above three pain behaviors, it was verified that the KSM is also suitable for the study of acupuncture analgesia. The analgesic effect of the opposing needling method is equivalent to the analgesic effect of acupuncture on the operated side, which is similar to the results in many other research researches [ 19 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, there are various acupuncture methods of treating pain diseases clinically, such as electroacupuncture (EA) [ 14 ], transcutaneous electrical acupuncture stimulation [ 15 ], auricular acupuncture [ 16 ], heat-sensitive moxibustion [ 17 ], and acupoint catgut embedding [ 18 ]. Opposing needling is used to treat pain in traditional Chinese medicine [ 19 , 20 ]. For unilateral TKA, the opposing needling method is more valuable in avoiding the risk of infection of acupuncture at the operated and adjacent area and increasing the patients' acceptance of acupuncture based on the overall characteristics of qi and blood flow in the whole body [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion was carried out for 15 min, five times per week for two weeks ( Figure 1(a) ) [ 18 ]. Before moxibustion, the fur on the moxibustion region was shaved to expose the bilateral ST36 (Zusanli acupoint, located 2 mm lateral to the anterior tubercle of the tibia in the anterior tibial muscle and 4 mm distal to the knee joint lower point).…”
Section: Methodsmentioning
confidence: 99%
“…The ST36 acupoint is located on the tibialis anterior muscle of the leg, and its functions in traditional oriental medicine are to fortify the spleen and stomach, replenish qi and nourish blood, clear and activate meridians, and nourish the channels [ 15 ]. Lots of pre-clinical works indicated that stimulations applied on this acupoint (e.g., BVA, electro-acupuncture, laser-acupuncture, or moxibustion) can produce significant pain-relieving effects under diverse conditions, such as neuropathic, incision, or inflammatory pain state [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%